Additional efficacy analysis of avatrombopag phase III data for the treatment of adults with immune thrombocytopenia. (31st December 2023) - Jain, Shivi; Gernsheimer, Terry; Kolodny, Scott; Bernheisel, Chelsea; Vredenburg, Michael; Panch, Sandhya R.
Abstract: Avatrombopag is an oral thrombopoietin receptor agonist (TPO-RA) that was approved in the US in 2019 for treatment of chronic immune thrombocytopenia (ITP). This post hoc analysis of the pivotal phase III study (NCT01438840) of avatrombopag in adult patients with ITP evaluated platelet count response to avatrombopag during the core study in different subgroups, and durability of response data in patients who responded to avatrombopag treatment both during the core phase (total population) and during the core and extension phase (total population and by subgroup). Loss of response (LOR [platelet count <30 × 10 9 /L]) was defined as LOR over two consecutive scheduled visits. The response was generally similar between subgroups though a few differences were observed. The durability of response analysis showed that avatrombopag-treated patients maintained their response for 84.5% of time on treatment during the core phase and 83.3% during the core and extension phase; 55.2% of patients in the core phase and 52.3% in the core and extension phase never experienced LOR. We conclude that the initial response to avatrombopag is both stable and durable. Plain Language Summary: What is the context? Avatrombopag is a medicine that helps the body produce platelet cells, which are necessary for blood clotting. Avatrombopag is used to treat people with chronic immune thrombocytopenia (ITP); these patients have low numbers of platelet cells in their blood, so their blood may not clot efficiently, putting them at risk of uncontrolled bleeding. A phase III clinical study in patients with chronic ITP showed that platelet counts increased for most patients who were treated with avatrombopag; patients who had a platelet count ≥50 × 10 9 /L were considered to have a response to avatrombopag treatment. The present study analyzes data from a phase III clinical study to determine whether there are any characteristics that make a patient more or less likely to have a loss of response (LOR) while taking avatrombopag, whether the initial response to avatrombopag is stable, and how long the response lasts. For this analysis, LOR is defined as platelet count <30 × 10 9 /L for either four consecutive weeks or for two consecutive office visits while taking avatrombopag. What is new? In general, patient characteristics did not influence the likelihood of LOR. Patients who responded maintained their response for most of the time they were taking avatrombopag. Most patients did not experience LOR. What is the impact? The initial response to avatrombopag is stable and long-lasting in patients with chronic ITP. These findings indicate that patients with a variety of background characteristics can experience a durable platelet response with avatrombopag treatment.